Association Between Circulating Proprotein Convertase Subtilisin/Kexin Type 9 Concentrations and Cardiovascular Events in Cardiovascular Disease: A Systemic Review and Meta-Analysis - Liu, Jiahui; Fan, Fangfang; Luo, Xingyu; Ji, Wenjun; Liu, Yaokun; Zhang, Yan; Zheng, Bo (Frontiers in Cardiovascular Medicine, 2021)
Background: Although a large amount of evidence has proved that proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors bring clinical benefits among cardiovascular disease (CVD) patients, whether the PCSK9 level predicts future CV events still remains ambiguous. Methods: We conducted a meta-analysis to investigate PCSK9 levels on prediction of future CV events among established CVD patients. Comprehensive search of electronic databases was conducted through June 2021. We included relative risk (RR) estimates with 95% confidence intervals (CI) or events of interest. Results: Totally, 11 cohort studies including 8471 CVD patients were enrolled. The pooling RR of the risk of CV events for an increase in circulating baseline PCSK9 by 1 - Standard Deviation (SD) exhibited positive association in a random-effect model (RR 1.226; 95%CI: 1.055 - 1.423, P = 0.008). Similarly, the total CV events risk increase of 52% for patients distributed in the highest tertile compared to lowest tertile of circulating PCSK9 (RR 1.523, 95% CI: 1.098 - 2.112, P = 0.012). The association between PCSK9 and CV events is obvious among stable CVD patients, patients treated with statin and Asian patients. Conclusions: High PCSK9 levels are significantly related with increased future CV events risk. These results enrich the knowledge of PCSK9 function and suggest more possible clinical role of PCSK9 inhibitors.